2005
DOI: 10.1177/0892705705049559
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene-grafted Carbon Fibers: Surface Properties and Adhesion to Polystyrene

Abstract: It is highly desirable to improve attractive interactions between carbon fibers and unreactive thermoplastic matrices to the possible maximum. This could be achieved by a simple grafting process to create a covalently bonded interface or interlayer, which should result in cohesive interactions between the polymer-grafted fibers and the same matrix material, leading to a better adhesion strength in the obtained composite material. Here, we are describing the grafting of styrene onto unmodified and unsized carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Note that this value is still at about the half that was measured for PP-sized GF in a PP matrix containing maleic anhydride grafted PP (PP-g-MA) that might be considered as the state-of-the-art coupling agent [82]. Bismarck et al [83] grafted polystyrene (PS) via bulk radical polymerization of styrene to CF surface. The contact angle and zeta-potential measurements confirmed that the surface of the grafted CF was PS-like.…”
Section: Polymer Graftingmentioning
confidence: 99%
“…Note that this value is still at about the half that was measured for PP-sized GF in a PP matrix containing maleic anhydride grafted PP (PP-g-MA) that might be considered as the state-of-the-art coupling agent [82]. Bismarck et al [83] grafted polystyrene (PS) via bulk radical polymerization of styrene to CF surface. The contact angle and zeta-potential measurements confirmed that the surface of the grafted CF was PS-like.…”
Section: Polymer Graftingmentioning
confidence: 99%
“…However, due to the un-reactive nature of thermoplastic polymers and the nature of commercially applied carbon fibre surface treatments, the adhesion between commercial fibres and thermoplastic matrices is usually low [21]. Therefore, additional modification techniques have been introduced in order to optimise the fibre/thermoplastic adhesion, which includes electro-coating [22] and polymer grafting [23,24]. The problem with these methods is that they require potentially harmful chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…CNFs have been successfully compounded with different thermoplastic14, 16, 18–31 and thermoset32, 33 matrices using conventional polymer processing technology such as high‐shear mixing or extrusion, demonstrating the feasibility of such methods for effective dispersion and orientation of the nanofibers. Unfortunately, the mechanical performance of these composites have been limited by the lack of an adequate interface strength, which results in poor interlaminar adherence and fiber pull‐out 15, 34…”
Section: Introductionmentioning
confidence: 99%